Congenital Adrenal Hyperplasia: A Case Report (Journal of Chittagong Medical College Teachers' Association, 2014)
Congenital adrenal hyperplasia (CAH) is rare condition with different presentations. The most important 'salt loosing' variant is a medical emergency. More than 90% of cases of congenital adrenal hyperplasia are caused by 21 a-hydroxylase deficiency (21aOH). Rather than cortisol, the adrenals produce excess sex hormone. Majority of patients cannot synthesize sufficient aldosterone. There is virilization of girls, rapid somatic growth with early epiphyseal fusion in both sexes and even life threatening hyponatremic dehydration. The present case presented on 5th postnatal day with unrecognized sex and repeated vomiting. The baby was hyperpigmented, dehydrated with ambiguous genitalia. Hyponatremic, hyperkalemic hypochloremic metabolic acidosis with normal renal profile was seen. Both adrenal glands were enlarged with presence of uterus. Serum cortisol level was low but testosterone level was very high. The newborn was treated as congenital adrenal hyperplasia with hydrocortisone, fludrocortisones, calcium gluconate and 10% dextrose in 0.45% NaCl solution. Significant clinical improvement was observed within a week in this case. The case was presented with a view to focus such rare medical emergency so that Pediatricians and Neonatologists could manage the problem timely.JCMCTA 2013 ; 24 (2): 44-47